READING INTEREST OF COLLEGE STUDENTS IN GONDIA DISTRICT: A STUDY - Meshram, Varsha M; Choudhary, Aparna S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research is based on learning the interest of college students of the Gondia district reading. The Reading interest is crucial and assists students in acquiring knowledge, honing language and thinking sharply. The research was carried out through gathering the responses of students in various colleges in Gondia. Structured questionnaire survey method was applied. Hypothesis testing and descriptive statistics were applied to analyse the data. The results indicate that majority of students enjoy reading textbooks during their studies, however, many also read newspapers, magazines literature and storybooks. Reading preferences are also influenced by the gender and stream of study. The paper is topped with the recommendations as to how Reading interests should be promoted among students.